"The S Word: A Practical Acting Laboratory": a practice-based research event. Issue 1 (2nd January 2019) - Merlin, Bella
ABSTRACT: In 2016, Drs. Paul Fryer (Stanislavski Centre, Rose Bruford College for Theatre and Performance) and Bella Merlin (department of Theatre, Film and Digital Production at the University of California, Riverside) co-created "The S Word", a series of international events intended to provoke new inquiry and stir up debate concerning Stanislavski's place in twenty-first-century acting. The third event was hosted at UCR in April 2018 and entitled, "The S Word: A Practical Acting Laboratory". It was framed as a practice-based research event, bringing together internationally acclaimed actor trainers Dr. Sharon M. Carnicke (Stanislavski expert and author of Stanislavsky in Focus ), Tina Packer (actor-director, and co-founder of Shakespeare & Company in Massachusetts) and Kimberly Guerrero (Native American actor, writer, storyteller and assistant professor of acting at UCR). This article follows the trajectory of the interdisciplinary weekend laboratory, including a 20-minute edit of The Culmination, the final sharing of research findings held on the concluding Sunday morning.